Pandora: nucleotide-resolution bacterial pan-genomics with reference graphs - Colquhoun, RM; Hall, MB; Lima, L; Roberts, LW; Malone, KM; Hunt, M; Letcher, B; Hawkey, J; George, S; Pankhurst, L; Iqbal, Z (BioMed Central, 2021)
We present pandora, a novel pan-genome graph structure and algorithms for identifying variants across the full bacterial pan-genome. As much bacterial adaptability hinges on the accessory genome, methods which analyze SNPs in just the core genome have unsatisfactory limitations. Pandora approximates a sequenced genome as a recombinant of references, detects novel variation and pan-genotypes multiple samples. Using a reference graph of 578 Escherichia coli genomes, we compare 20 diverse isolates. Pandora recovers more rare SNPs than single-reference-based tools, is significantly better than picking the closest RefSeq reference, and provides a stable framework for analyzing diverse samples without reference bias.